Efficient humidifying film under high gas flow working condition and preparation method of efficient humidifying film
By designing a high-efficiency humidification membrane under high gas flow conditions, including dense inner surface cortex, double-layer finger-like intermediate layer and nanopore outer surface layer, the low humidity efficiency of fuel cell humidification systems under high gas flow conditions is solved and The major problem of gas leakage has achieved efficient humidity enhancement and low gas leakage.
Patent Information
- Application Number
- CN202411527150.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-14
AI Technical Summary
The fuel cell humidification system has low humidity efficiency and large gas leakage at high gas flow, resulting in a degradation of fuel cell performance.
A high-efficiency humidification film under high gas flow conditions was designed, including a dense inner surface cortex, an intermediate layer and an outer surface nanopore layer. The cross-section of the intermediate layer is a double-layer finger-like pore structure, and the sponge layer enhances the mechanical properties of the fiber membrane.
Under high gas flow, the humidity increase efficiency can reach 40%-60%, and the gas leakage is less than 1L/min, ensuring the stable operation of the fuel cell system.
Smart Images

Figure CN119425412A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thin film materials, and in particular to a high-efficiency humidification membrane under high gas flow conditions and a preparation method thereof. Background Art
[0002] In the context of the global active search for sustainable energy solutions, fuel cells have become an important development direction for future energy due to their high efficiency and environmental protection. The performance of the proton exchange membrane, the core component of the fuel cell, depends on a suitable humidity environment. Low humidity conditions will reduce its ion conductivity, resulting in a decrease in fuel cell power. Under high humidity conditions, water flooding is prone to occur in the porous electrode structure, causing blockage of the gas diffusion layer and thus causing a decrease in battery performance. Therefore, a humidification system is required to regulate the water content and distribution inside the fuel cell to maintain the high conductivity and durability of the proton exchange membrane. Among them, the membrane humidification system has gradually become one of the hot spots in the field of fuel cell research due to its advantages such as simple structure, light weight, and no parasitic power.
[0003] One side of the membrane humidification system is dry and cold fuel gas, and the other side is humid and hot exhaust gas. With the concentration difference as the driving force, water vapor diffuses freely through the porous membrane to achieve the purpose of wet heat exchange between exhaust gas and dry and cold air. Air tightness and humidification performance are important indicators for evaluating humidification membranes. Good air tightness helps to accurately control gas flow and pressure to ensure the stability of fuel cell system operation; higher humidification performance can greatly reduce the area of humidification membrane, thereby reducing the space occupied by fuel cells. The patent with application number CN202111397123.X discloses a preparation method and application of a leakproof humidification composite hollow fiber membrane, but the preparation process requires hydrophobic modification of the inner surface, which is relatively complicated, and the internal hydrophobic structure has a large resistance to the water vapor diffusion process, and the water vapor mass transfer flux is low at a higher gas flow rate; Chinese patent CN103551059B discloses a mixed matrix membrane prepared by blending perfluorosulfonic acid ion exchange resin with highly absorbent plastic staple fibers, but the expensive cost of perfluorosulfonic acid ion exchange resin has become the main obstacle to the development of the membrane. Chinese patent CN115463550A prepares a polyethersulfone humidification membrane with an asymmetric structure. Inorganic particles such as silicon dioxide and titanium dioxide are introduced during the preparation process. During actual operation, it is easy to be entrained by high-flow gas into the fuel cell stack, thereby reducing the operating efficiency of the fuel cell system. Summary of the invention
[0004] The purpose of the present invention is to overcome the above-mentioned technical deficiencies, provide a high-efficiency humidification membrane and a preparation method thereof under high gas flow conditions, and solve the technical problems in the prior art that the humidification efficiency of the fuel cell humidification system is low and the gas leakage is large under high gas flow (2000L / h-12000L / h).
[0005] The present invention provides a high-efficiency humidification membrane under high gas flow conditions, comprising an inner surface cortex, an intermediate layer and an outer surface nanoporous layer arranged in sequence from the inside to the outside, wherein the surface pore structure of the inner surface cortex is a slit pore, and the relatively dense internal cortex helps to maintain a low gas leakage rate under high gas flow, and prevents the dry gas side flow fluctuation and the generation of insufficient raw gas due to gas leakage. The surface pore structure of the outer surface nanoporous layer is circular, and the pore structure helps water molecules enter the porous membrane through the capillary condensation mechanism, thereby promoting the diffusion of water molecules. The cross section of the intermediate layer is a double-layer finger-like pore structure, and the intermediate layer includes a first membrane layer, a sponge layer and a second membrane layer, and the average pore size of the second membrane layer is greater than the average pore size of the first membrane layer. The larger cross-sectional pore structure reduces the mass transfer resistance of water vapor in the membrane pores and increases the water vapor transfer flux. The sponge layer is between the double finger-like pore structures in the cross section, which can enhance the mechanical properties of the fiber membrane to ensure the stability of the fiber membrane under high gas flow.
[0006] Preferably, one side of the first membrane layer is connected to the inner surface skin layer and the other side is connected to the sponge layer, and one side of the second membrane layer is connected to the sponge layer and the other side is connected to the outer surface nanoporous layer.
[0007] Preferably, the pore size of the first finger-shaped pores inside the first membrane layer gradually increases from the inner surface cortex to the sponge layer; the pore size of the second finger-shaped pores inside the second membrane layer gradually increases from the outer surface nanoporous layer to the sponge layer.
[0008] Preferably, the average pore size of the inner surface cortical layer is 0.01-0.5 nm, and the average pore size of the outer surface nanoporous layer is 2-10 nm.
[0009] Preferably, the thickness of the intermediate layer is 100-120 μm, and the average pore diameters of the first finger-shaped holes and the second finger-shaped holes are 10-20 μm.
[0010] A method for preparing the high-efficiency humidification membrane described above comprises the following steps:
[0011] S1, mixing a high molecular polymer, a first additive, a second additive and / or a solvent to obtain a spinning solution;
[0012] S2, the spinning solution and the core solution are co-extruded in a spinneret for spinning, and a coagulation bath is performed after pre-phase separation to obtain a hollow fiber membrane. The air pre-phase separation process can stabilize the fiber morphology and prevent the fiber from deforming and collapsing under the action of gravity and surface tension;
[0013] S3, stretching the hollow fiber membrane, washing it with water, and drying it to obtain a high-efficiency humidification membrane.
[0014] Preferably, the spinning solution in S1 comprises, by mass, 18 to 25 parts of the high molecular polymer, 0.5 to 5 parts of the first additive, 5 to 12.5 parts of the second additive, and 61 to 75 parts of the solvent.
[0015] Preferably, the high molecular polymer in S1 is one or more of polysulfone, sulfonated polysulfone, polyarylsulfone, polyethersulfone, sulfonated polyethersulfone, polyvinylidene fluoride, and cellulose acetate; the first additive and the second additive both act as porogens, and a porous hollow fiber membrane with a suitable surface pore structure and pore size distribution is obtained by adjusting the diffusion rate during the phase inversion process, and the first additive is one of water, polyvinyl alcohol, butyrolactone, and acetic acid; the second additive is one of polyethylene glycol, polyvinyl pyrrolidone, and polyethyleneimine; the solvent is one of dimethyl sulfoxide, NN dimethylformamide, NN dimethylacetamide, and N-methylpyrrolidone.
[0016] Preferably, the core liquid in S2 is distilled water, and the core liquid temperature is 30°C-40°C. When the core liquid is water and the coagulation bath contains a certain solvent, the inner surface of the hollow fiber membrane coagulates and precipitates quickly to form a surface separation layer. The organic solvent concentration in the coagulation bath is relatively high, which effectively delays the phase separation process and obtains a relatively loose pore structure.
[0017] Preferably, the solution used in the coagulation bath in S2 is one or more of dimethyl sulfoxide, N-N dimethylformamide, N-N dimethylacetamide, and N-methylpyrrolidone.
[0018] In the membrane humidification system, the pressure on the dry gas side is greater than 100KPa, the flow rate on the dry gas side is 2000L / h-12000L / h, and the wet gas side is supersaturated wet gas with a pressure greater than 70KPa. Pressure driving cannot be implemented during the diffusion of water vapor. It uses concentration difference as the driving force for mass transfer, freely diffuses into the porous membrane through capillary condensation, and is carried away by air on the dry gas side to play a humidification role. The nanoscale pore structure on the outer surface of the high-efficiency humidification membrane of the present invention helps water vapor enter the membrane pores, so that it has a good humidification efficiency. At this gas flow rate, the humidification efficiency of the present invention can reach 40%-60%. The gas leakage of dry gas at this operating pressure is less than 1L / min. On the one hand, the pore size of the dense cortex on the inner surface is small, which can effectively prevent gas diffusion. In addition, the capillary condensation of water vapor can form a layer of liquid water on the surface of the dry gas, which can effectively prevent gas from passing through, thereby increasing air tightness.
[0019] Compared with the prior art, the beneficial effects of the present invention include:
[0020] The high-efficiency humidifying membrane of the present invention has a dense inner surface skin layer, a porous outer surface skin layer, a cross-section double-finger-shaped pore, and a sponge hole sandwich structure. The dense inner surface skin layer is conducive to reducing gas leakage under high gas flow, the porous outer surface skin layer has a capillary condensation effect on the water vapor on the wet side, the cross-section double-finger-shaped pore structure is conducive to gas diffusion, and the sponge hole sandwich structure can enhance the mechanical properties of the fiber membrane and realize long-term operation of the humidification system.
[0021] The present invention also provides a method for preparing a high-efficiency humidification membrane, which can be used in a fuel cell humidification system. The preparation method is simple, and the prepared film can maintain low gas leakage and high humidification efficiency under high dry gas side flow, and has better air tightness and humidification capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a schematic structural diagram of a high-efficiency humidification membrane under high gas flow conditions provided in Example 1 of the present invention;
[0023] Figure 2 It is a schematic diagram of the partial structure of a high-efficiency humidification membrane under high gas flow conditions provided in Example 1 of the present invention;
[0024] Figure 3 This is a SEM image of the inner surface of a high-efficiency humidification membrane under high gas flow conditions provided in Example 1 of the present invention;
[0025] Figure 4 This is a SEM image of the outer surface of a high-efficiency humidification membrane under high gas flow conditions provided in Example 1 of the present invention;
[0026] Figure 5 This is a cross-sectional SEM image of a high-efficiency humidification membrane under high gas flow conditions provided in Example 1 of the present invention.
[0027] Among them: inner surface skin layer 1, middle layer 2, first membrane layer 21, sponge layer 22, second membrane layer 23, outer surface nanoporous layer 3. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0029] Example 1
[0030] like Figure 1 , Figure 2As shown, a high-efficiency humidification membrane under high gas flow conditions includes an inner surface skin layer 1, an intermediate layer 2 and an outer surface nanoporous layer 3 arranged in sequence from the inside to the outside, the surface pore structure of the inner surface skin layer 1 is a slit hole, the surface pore structure of the outer surface nanoporous layer 3 is circular, the cross-section of the intermediate layer 2 is a double-layer finger-like pore structure, the intermediate layer 2 includes a first membrane layer 21, a sponge layer 22 and a second membrane layer 23, and the average pore size of the second membrane layer 23 is larger than the average pore size of the first membrane layer 21.
[0031] One side of the first membrane layer 21 is connected to the inner surface skin layer 1 and the other side is connected to the sponge layer 22 . One side of the second membrane layer 23 is connected to the sponge layer 22 and the other side is connected to the outer surface nanoporous layer 3 .
[0032] The pore size of the first finger-shaped pores inside the first membrane layer 21 gradually increases from the inner surface skin layer 1 to the sponge layer 22; the pore size of the second finger-shaped pores inside the second membrane layer 23 gradually increases from the outer surface nanoporous layer 3 to the sponge layer 22.
[0033] The average pore size of the inner surface skin layer 1 may be 0.01-0.5 nm, and the average pore size of the outer surface nanoporous layer 3 may be 2-10 nm. In this embodiment, the average pore size of the inner surface skin layer 1 is 0.3 nm, and the average pore size of the outer surface nanoporous layer 3 is 6 nm.
[0034] The thickness of the sponge layer 22 may be 10-30 μm, and the average pore size of the first finger-shaped holes and the second finger-shaped holes may be 5-30 μm. In this embodiment, the thickness of the sponge layer 22 is 20 μm, and the average pore size of the first finger-shaped holes and the second finger-shaped holes may be 15 μm.
[0035] A method for preparing a high-efficiency humidification membrane in this embodiment comprises the following steps:
[0036] (1) Preparation of spinning solution: The spinning solution is prepared according to 19 wt % polysulfone, 1 wt % water, 5 wt % polyvinyl pyrrolidone, and 75 wt % N-methyl pyrrolidone, wherein the polysulfone is vacuum dried at 60° C. for 24 h before use, and the spinning solution is mechanically stirred for 24 h and then allowed to stand for degassing for 48 h for use;
[0037] (2) Preparation of hollow fiber membrane: The spinning solution and core liquid are co-extruded from the spinneret and enter the coagulation bath after a 1 s air pre-phase separation process, wherein the core liquid is an aqueous solution, the coagulation bath is a 75% N-methylpyrrolidone aqueous solution, the core liquid temperature is 40°C, and the coagulation bath temperature is 55°C.
[0038] (3) Post-treatment process: The hollow fiber membrane is stretched 1.5 times, and then continuously washed with water and dried to obtain an efficient humidification membrane under high gas flow conditions.
[0039] The relevant microstructure of the high-efficiency humidification membrane prepared in this embodiment is shown in Figure 3-5 As shown, it can be seen that the outer surface of the high-efficiency humidification membrane prepared by the method in this embodiment is a nanoporous structure, the inner surface is a dense cortex, and the cross-section is a double-finger-shaped pore sandwiched with a sponge pore structure.
[0040] Example 2
[0041] The high-efficiency humidification membrane in this embodiment is similar to that in embodiment 1. This embodiment provides a method for preparing a high-efficiency humidification membrane, comprising the following steps:
[0042] (1) Preparation of spinning solution: The spinning solution is prepared according to 25 wt% polyethersulfone, 0.5 wt% water, 6 wt% polyvinylpyrrolidone, and 68.5 wt% NN dimethylacetamide, wherein the polyethersulfone is vacuum dried at 60°C for 24 h before use. The spinning solution is mechanically stirred for 24 h and then allowed to stand for degassing for 48 h for use.
[0043] (2) Preparation of hollow fiber membrane: The spinning solution and core liquid are co-extruded from the spinneret and enter the coagulation bath after a 2 s air pre-phase separation process, wherein the core liquid is an aqueous solution, the coagulation bath is a 60 wt% NN dimethylacetamide aqueous solution, the core liquid temperature is 30°C, and the coagulation bath temperature is 35°C.
[0044] (3) Post-treatment process: The hollow fiber membrane is stretched 2 times, and then continuously washed with water and dried to obtain an efficient humidification membrane under high gas flow conditions.
[0045] Example 3
[0046] The high-efficiency humidification membrane in this embodiment is similar to that in embodiment 1. This embodiment provides a method for preparing a high-efficiency humidification membrane, comprising the following steps:
[0047] (1) Preparation of spinning solution: The spinning solution is prepared according to 20 wt% polyvinylidene fluoride, 1.5 wt% polyvinyl alcohol, 12.5 wt% polyethylene glycol 600, and 66 wt% NN dimethylformamide. The polyvinylidene fluoride is vacuum dried at 60°C for 24 h before use. The spinning solution is mechanically stirred for 24 h and then allowed to stand for degassing for 48 h for use.
[0048] (2) Preparation of hollow fiber membrane: The spinning solution and core liquid are co-extruded from the spinneret and enter into a coagulation bath after 2.7 s of air pre-phase separation, wherein the core liquid is an aqueous solution and the coagulation bath is a 50 wt% NN dimethylformamide aqueous solution. The core liquid temperature is 29°C and the coagulation bath temperature is 35°C.
[0049] (3) Post-treatment process: The hollow fiber membrane is stretched 3 times, and then continuously washed with water and dried to obtain an efficient humidification membrane under high gas flow conditions.
[0050] Example 4
[0051] The high-efficiency humidification membrane in this embodiment is similar to that in embodiment 1. This embodiment provides a method for preparing a high-efficiency humidification membrane, comprising the following steps:
[0052] (1) Preparation of spinning solution: The spinning solution is prepared according to 18 wt% polysulfone, 5% water, 50 wt% polyethylene glycol 600, and 72 wt% NN dimethylformamide, wherein the polysulfone is vacuum dried at 60°C for 24 h before use. The spinning solution is mechanically stirred for 24 h and then allowed to stand for degassing for 48 h for use.
[0053] (2) Preparation of hollow fiber membrane: The spinning solution and core liquid are co-extruded from the spinneret and enter the coagulation bath after 1 s of air pre-phase separation process, wherein the core liquid is an aqueous solution, the coagulation bath is a 50 wt% NN dimethylformamide aqueous solution, the core liquid temperature is 30°C, and the coagulation bath temperature is 35°C.
[0054] (3) Post-treatment process: The hollow fiber membrane is stretched 3 times, and then continuously washed with water and dried to obtain an efficient humidification membrane under high gas flow conditions.
[0055] Example 5
[0056] This embodiment is similar to embodiment 1, except that the mass fraction of polysulfone in the spinning solution in this embodiment is 22 wt %, and the mass fraction of N-methylpyrrolidone is 72 wt %.
[0057] Example 6
[0058] This embodiment is similar to embodiment 1, except that the mass fraction of polysulfone in the spinning solution in this embodiment is 25 wt % and the mass fraction of N-methylpyrrolidone is 69 wt %.
[0059] Example 7
[0060] This embodiment is similar to embodiment 2, except that in this embodiment, 20 wt% polyethersulfone, 1.5 wt% butyrolactone, 6.5 wt% polyvinylpyrrolidone, and 72 wt% NN dimethylacetamide are selected in the spinning solution.
[0061] Example 8
[0062] This embodiment is similar to embodiment 3, except that 25 wt% polyvinylidene fluoride and 61 wt% NN dimethylformamide are used in the spinning solution in this embodiment.
[0063] Comparative Example
[0064] This comparative example provides a method for preparing a humidifying membrane, comprising the following steps:
[0065] (1) Preparation of spinning solution: The spinning solution was prepared according to 15 wt% polysulfone, 16 wt% polyethylene glycol 600, and 69 wt% N-methylpyrrolidone, wherein the polysulfone was vacuum dried at 60°C for 24 h before use. The spinning solution was mechanically stirred for 24 h and then allowed to stand for degassing for 48 h for use.
[0066] (2) Preparation of hollow fiber membrane: The spinning solution and core liquid are co-extruded from the spinneret and enter the coagulation bath after a 1 s air pre-phase separation process. The core liquid is an aqueous solution and the coagulation bath is water. The core liquid temperature is 40°C and the coagulation bath temperature is 55°C.
[0067] (3) Post-treatment process: The hollow fiber membrane is stretched 1.5 times, then continuously washed with water, and dried for use.
[0068] The humidifying membranes prepared in Examples 1-8 and Comparative Examples were made into humidifier components, and the dry gas flow was placed under an air pressure of 100KPa to measure the gas leakage of the humidifier, and then placed in a humidifier test bench to measure the humidification efficiency of the humidifier under a given gas flow rate. The test conditions were: dry gas flow rate 7000L / h, dry gas pressure 120KPa, dry gas temperature 80°C, wet gas pressure 80KPa, wet temperature 90°C. The calculation formula is as follows:
[0069] Absolute humidity calculation:
[0070]
[0071] Where: AH—absolute humidity g / cm 3
[0072] e—water vapor pressure Pa 1Pa=0.01hPa
[0073] R w —Gas constant of water R w =461.52J / (Kg*k)
[0074] T—temperature k T=t+273.15
[0075] t—air temperature ℃
[0076] m—mass of dissolved water in the air g
[0077] V—air volume cm 3
[0078] Calculate the moisture transfer efficiency:
[0079]
[0080] Where: WTE—water transfer efficiency %
[0081] AHwet out —Absolute humidity at wet outlet g / cm 3
[0082] AH dryin —Dry inlet absolute humidity g / cm 3
[0083] AH Exhaust in —Exhaust gas inlet absolute humidity g / cm 3
[0084] The humidification performance was calculated according to the above formulas (1), (2) and (3), and the results are shown in Table 1.
[0085] Table 1 Humidification performance test results
[0086]
[0087]
[0088] From the test results in Table 1, it can be seen that the humidification membrane in the comparative example has a higher gas leakage rate because its inner surface has no dense cortex, and the pure finger-like pore structure has lower mechanical properties. Although its humidification effect is good, it is not suitable for the fuel cell humidifier system. The gas leakage rate of Examples 1-8 is low, and the dry gas outlet humidity can be maintained at 40%-70% under high gas flow conditions. The mechanical properties are high, which is conducive to achieving a continuous and stable hydrogen fuel cell humidification process.
[0089] The performance of the humidifying membrane prepared by replacing the polysulfone in the spinning solution in Example 1 with sulfonated polysulfone or sulfonated polyethersulfone or cellulose acetate is the same as that in Example 1.
[0090] The performance of the humidifying membrane prepared by replacing the water in the spinning solution in Example 1 with acetic acid, polyvinyl pyrrolidone with polyethyleneimine, N-methyl pyrrolidone with dimethyl sulfoxide, and the solution used in the coagulation bath with dimethyl sulfoxide is the same as that in Example 1.
[0091] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A high-efficiency humidification membrane under high gas flow conditions, characterized in that: It includes an inner surface cortex, an intermediate layer and an outer surface nanoporous layer which are arranged in sequence from the inside to the outside. The surface pore structure of the inner surface cortex is a slit pore, the surface pore structure of the outer surface nanoporous layer is circular, the cross section of the intermediate layer is a double-layer finger-like pore structure, the intermediate layer includes a first membrane layer, a sponge layer and a second membrane layer, and the average pore size of the second membrane layer is larger than the average pore size of the first membrane layer.
2. The high-efficiency humidification membrane under high gas flow conditions according to claim 1, characterized in that: One side of the first membrane layer is connected to the inner surface skin layer and the other side is connected to the sponge layer. One side of the second membrane layer is connected to the sponge layer and the other side is connected to the outer surface nanoporous layer.
3. The high-efficiency humidification membrane under high gas flow conditions according to claim 2, characterized in that: The pore size of the first finger-shaped pores inside the first membrane layer gradually increases from the inner surface cortex to the sponge layer; the pore size of the second finger-shaped pores inside the second membrane layer gradually increases from the outer surface nanoporous layer to the sponge layer.
4. The high-efficiency humidification membrane under high gas flow conditions according to claim 1, characterized in that: The average pore size of the inner surface cortex is 0.01-0.5 nm, and the average pore size of the outer surface nanoporous layer is 2-10 nm.
5. The high-efficiency humidification membrane under high gas flow conditions according to claim 1, characterized in that: The thickness of the sponge layer is 10-30 μm, and the average pore diameters of the first finger-shaped pores and the second finger-shaped pores are 5-30 μm.
6. A method for preparing a high-efficiency humidifying membrane according to any one of claims 1 to 5, characterized in that: The steps include: S1, mixing a high molecular polymer, a first additive, a second additive and / or a solvent to obtain a spinning solution; S2, co-extruding the spinning solution and the core solution in a spinneret for spinning, and performing a coagulation bath after pre-phase separation to obtain a hollow fiber membrane; S3, stretching the hollow fiber membrane, washing it with water, and drying it to obtain a high-efficiency humidification membrane.
7. The preparation method according to claim 6, characterized in that: The spinning solution in S1 includes 18 to 25 parts of a high molecular polymer, 0.5 to 5 parts of a first additive, 5 to 12.5 parts of a second additive, and 61 to 75 parts of a solvent, in parts by mass.
8. The preparation method according to claim 6, characterized in that: The high molecular polymer described in S1 is one or more of polysulfone, sulfonated polysulfone, polyarylsulfone, polyethersulfone, sulfonated polyethersulfone, polyvinylidene fluoride, and cellulose acetate; the first additive is one of water, polyvinyl alcohol, butyrolactone, and acetic acid; the second additive is one of polyethylene glycol, polyvinyl pyrrolidone, and polyethyleneimine; the solvent is one of dimethyl sulfoxide, NN dimethylformamide, NN dimethylacetamide, and N-methylpyrrolidone.
9. The preparation method according to claim 6, characterized in that: The core liquid in S2 is distilled water, and the temperature of the core liquid is 30°C-40°C.
10. The preparation method according to claim 6, characterized in that: The solution used in the coagulation bath in S2 is one or more of dimethyl sulfoxide, N-N dimethylformamide, N-N dimethylacetamide, and N-methylpyrrolidone.
Citation Information
Patent Citations
Fiber tube type moisture permeable film and preparation method thereof
CN103551059B
Leakproof humidifying composite hollow fiber membrane as well as preparation method and application thereof
CN113926316A
Polyether sulfone humidifying film with symmetrical structure and preparation method thereof
CN115463550A